Building Public Support for Anti-obesity Policy Initiatives - Bruce Silverglade (HealthcarePapers, 2008)
Solving the obesity crisis has less to do with post-partisanship and more to do with increasing public support for strong public policy initiatives that will make the healthy choice the easy choice. The government has an important role in mitigating the toxic food environment created by food manufacturers and restaurant chains. Progress to date has occurred on the state level. With greater public support in a new political environment, national progress may be possible in the foreseeable future.
Keywords: Obesity Crisis, Public Policy, healthy choices, toxic food environment